Team Creativity, Cognition, and Cognitive Style Diversity - Aggarwal, Ishani; Woolley, Anita Williams (Management Science, 2019)
In spite of the recognized importance of team creativity for organizational success, the factors that influence it are not well understood. In this paper, we address an important gap in the literature on the impact of team diversity on team creativity. We show how team cognitive diversity both enhances and inhibits team cognition, or the manner in which information is organized and distributed within the team. We further demonstrate that team cognition is a key mechanism through which cognitive diversity influences team creativity. The paper introduces a new theoretical lens, the signal-detection perspective, which argues that cognitive diversity amplifies the signals to the location of critical cognitive resources within the team and aids in their detection, consequently enhancing the form of team cognition that is central to team creativity. We test the predictions in a longitudinal study with 112 MBA student project teams. This research advances our understanding of what makes teams creative by synthesizing and testing existing theory as well as providing a new perspective that highlights an alternative way in which a team’s cognitive inputs impact team creativity. This paper was accepted by Sendil Ethiraj, organizations.